Cardiovascular outcomes after percutaneous coronary intervention on bifurcation lesions with moderate to severe coronary calcium: A single‐center registry study. Issue 1 (10th June 2020) - Murphy, Jonathan Luke; Patel, Nileshkumar; Vengrenyuk, Yuliya; Okamoto, Naotaka; Barman, Nitin; Sweeny, Joseph; Kapur, Vishal; Hasan, Choudhury; Krishnan, Prakash; Vijay, Pooja; Jhaveri, Vaishvi; Dangas, George; et al.
Abstract: Background: Both target vessel calcification and target vessel bifurcation are associated with worse outcomes following percutaneous coronary intervention (PCI). Whether these entities in combination interact to influence outcomes after PCI of complex coronary disease is not known. Objectives: This study evaluated the association of target vessel bifurcation and target vessel calcification, alone and in combination, with adverse events following PCI. Methods: Registry data from 21, 165 patients who underwent PCI with drug‐eluting stents (DES) between January 2009 and December 2017 were analyzed. Patients were divided into four groups according to the presence or absence of target vessel bifurcation and presence of none/mild or moderate/severe target vessel calcification on angiography. Associations between lesion groups and 1 year major adverse cardiac events (MACE) were examined using Cox regression analysis. Results: At 1 year, unadjusted rates of MACE, death, myocardial infarction (MI), as well as stent thrombosis were highest in the group with both bifurcation lesion and moderate/severe calcification. After adjusting for confounders such as age, renal disease, and smoking, hazard ratios for MACE were 1.14 (95%CI 0.99–1.33) for bifurcation with none/mild calcification, 1.21 (95%CI 1.06–1.38) for no bifurcation and moderate/severe calcification, and 1.37 (95%CI 1.14–1.64) for bifurcation and moderate severe calcification, compared to patients with no bifurcation and none/mild calcification. Conclusions: The presence of a bifurcating target vessel with moderate/severe calcification is associated with a higher risk of adverse outcomes than either attribute alone. New approaches are needed to improve outcomes in this subset of patients with complex coronary artery disease.